Development of learning algorithms for fully connect layers of convolutional neural network - Wang, Yiming (Nanyang Technological University, 2020)
In the field of transfer learning, pre-trained weights are usually used in the Convolutional Layers to get the features of the data and Fully Connected Layers are trained again for another classification task based on new training data.